Rethinking Teacher Professionalism in ELT: A Theoretical Review Toward Adaptive and Future-Oriented Pedagogy - Nisa, Fauziatun; Thoyyibah, Elok Abidatut; Zebua, Wirda Ningsi (Proceeding International Conference on Education, 2025)
This study examines teacher professionalism from a theoretical perspective and its implications for English Language Teaching (ELT) in response to rapid digital transformation, curriculum shifts, and learner diversity. Drawing on a thematic analysis of 20 scholarly articles published between 2021 and 2025, the data were gathered using Publish or Perish (PoP), which retrieves sources from Google Scholar and CrossRef. The reviewed literature reflects current trends and issues in ELT, particularly within the theme “Bridging the Future: Innovating Education through Adaptive Pedagogies.” Findings reveal that teacher professionalism extends beyond the four basic competencies pedagogical, professional, social, and personal to include reflective practice, digital literacy, and adaptive thinking. Strategic approaches such as continuous professional development (CPD), blended learning, peer collaboration, and leadership development are identified. Despite these, challenges persist, including unequal access to training, administrative burden, and gender-related barriers. The study emphasizes the need for inclusive, integrated, and technology-responsive CPD models to empower teachers as adaptive change agents in the evolving ELT landscape.